2020
DOI: 10.1590/1414-431x202010067
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative effect of mifepristone (RU486) on human neuroblastoma cells (SK-N-SH): in vitro and in vivo studies

Abstract: RU486 (mifepristone), a glucocorticoid and progesterone receptor antagonist, has been reported to exert antiproliferative effects on tumor cells. Experiments were performed to analyze the effects of RU486 on the proliferation of the human neuroblastoma, both in vitro and in vivo, using the human neuroblastoma SK-N-SH cell line. The exposure in vitro of SK-N-SH cells to RU486 revealed a dose-dependent inhibition of 3 H-thymidine incorporation due to a rapid but persistent inhibition of MAPKinase activity and ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Currently, this compound is an approved for early pregnancy termination 6 . However, several studies have indicated the potential of mifepristone to exert anti-tumor effects in specific types of cancers, including breast cancer 7 , non-small cell lung cancer 8 , prostate cancer 9 , ovarian cancer 10 , glioblastoma 11 , and neuroblastoma 12 . In a DMBA-induced mammary tumor model, mifepristone treatment resulted in a reduction in tumor incidence, multiplicity, and size 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, this compound is an approved for early pregnancy termination 6 . However, several studies have indicated the potential of mifepristone to exert anti-tumor effects in specific types of cancers, including breast cancer 7 , non-small cell lung cancer 8 , prostate cancer 9 , ovarian cancer 10 , glioblastoma 11 , and neuroblastoma 12 . In a DMBA-induced mammary tumor model, mifepristone treatment resulted in a reduction in tumor incidence, multiplicity, and size 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%